Field-Testing Reusable Learning Objects Related to Sensory Over-Responsiveness - Lloyd, Kimberly; Seikel, Anthony; Moholy, Kiersten; Gee, Bryan M (The Open Journal of Occupational Therapy, 2015)
Background. There is an increased need for dynamic, mobile, and relevant parent and caregiver education related to autism spectrum disorders (ASD) and Sensory Processing (SP). This need may be due to the increased incidence of the conditions co-morbidity and the revision of the diagnostic criteria of ASD. Reusable learning objects (RLOs) have been implemented as instructional tools as a part of, or adjunct to, formal health care education programs. However, there is a lack of knowledge regarding the appropriateness of RLOs as a part of routine patient and caregiver instruction of children with ASD. Method. A semi-structured interview/rating scale was implemented among three practicing occupational therapists to ascertain their opinions regarding six prototype RLOs related to sensory processing for caregivers of children with ASD. Results. The participants perspectives revealed that the SP-based prototype RLOs were a viable and valuable option to be included as a resource for parents and caregivers of children with ASD. Conclusion. The findings of this study suggest that RLOs related to SP were valuable, especially related to their subject matter, accessibility, and reusability. Furthermore, the participants indirectly identified the strengths related to the foundational concepts of RLOs and how they could be applied to other therapeutic and behavioral topics for parents and caregivers of children with ASD.